A cloned DNA probe for Cowdria ruminantium hybridizes with eight heartwater strains and detects infected sheep. - Mahan, S M (1992)
The DNA probe pCS20, which was cloned from the DNA of the Crystal Springs heartwater strain from Zimbabwe, cross-reacted with DNAs of heartwater strains from all endemic areas, including four heartwater strains from Zimbabwe, two strains from South Africa, one strain from Nigeria, and the Gardel strain from the Caribbean island of Guadeloupe. By nucleic acid hybridization, the pCS20 DNA probe detected Cowdria ruminantium DNA in all DNA preparations made from plasma samples from infected sheep before and during the febrile reaction. Synthetic oligonucleotides were prepared for amplification of specific C. ruminantium DNA sequences by the polymerase chain reaction (PCR). Amplification of two DNA products (181 and 279 bp) from pCS20 DNA and C. ruminantium genomic DNA of heartwater strains was demonstrated. In contrast, amplification of these products or any other products was not possible from genomic DNAs of Anaplasma marginale, Babesia bigemina, Trypanosoma brucei brucei, Escherichia coli, and bovine endothelial cells. The cross-reactivities of the 32P-labeled PCR products with genomic DNAs from several heartwater strains were similar to those with the pCS20 DNA probe. A nucleic acid-based test that uses hybridization assays and PCR provides a sensitive method for the detection of heartwater in both animals and ticks and has applications in epidemiological studies for the disease, which may allow for improved disease control.